Risk factors of hearing loss among preschool children in Hanoi, Vietnam - Tuyet Xuong, Nguyen; Tran, Van Dinh (International Journal Of Community Medicine And Public Health, 2019)
Background: Risk factors of hearing loss among preschool children is still unknown in Vietnam. This study was to assess the risk factors of hearing loss among preschool children in Hanoi, Vietnam. Methods: A case-control study was conducted in Hanoi, Vietnam. A total of 314 hearing loss cases (aged 2-5 years) and 628 controls, frequency matched by age and sex, were selected. Information about prenatal, perinatal, and postnatal factors the children were obtained from direct interview using a questionnaire. Unconditional logistic regression analyses were performed to assess the association between different factors and hearing loss condition of children. Results: The results found five risk factors of hearing loss among preschool children, including maternal rubella (adjusted Odds ratio [OR]=11.72, 95%CI: 2.90-47.33), prolonged oxygen use (adjusted OR (95%CI: 2.72-70.82), severe jaundice (adjusted OR=13.47, 95%CI=5.09-35.59), meningitis (adjusted OR=26.44, 95%CI=5.65-123.59), and chronic ear infections (adjusted OR=14.03, 95%CI: 9.85-19.97). Conclusions: Different risk factors of hearing loss among preschool children in Hanoi found, including maternal rubella, prolonged oxygen use, severe jaundice, meningitis, and chronic ear infections. Studies regarding the prevention of hearing loss among children are urgently needed.